ORANG TUA MENOLAK VAKSINASI COVID - 19 UNTUK ANAK SEKOLAH DASAR - Ernanda, Wilda Ayu (Education For All, 2022)
This article discusses a problem that exists in the services that exist in a school institution, where schools must meet a requirement with the existence of services from the health office for elementary school children. Where this service is very important for health, especially for elementary.